Continuing revelation and institutionalization: Joseph Smith, Ralph Waldo Emerson and charismatic leadership in Antebellum America - Jetter, Claudia (Inspiration and institution in Christian history, 2021)
Nineteenth-century North American religious history is filled with divinely inspired people who received and recorded new revelations. This article presents Joseph Smith Jr and Ralph Waldo Emerson as charismatic prophets who promoted the idea of continuing revelation. Drawing on Max Weber's concept of charismatic authority, it will contrast their forms of new sacred writing with one another to show how both had experienced encounters with the divine. The second part will then explore how different conceptualizations of revelation led to opposing concepts of religious authority, with consequences for the possibility of institution-building processes. While Smith would reify revelation in hierarchy, Emerson eventually promoted extreme spiritual individualization by rejecting the idea of an exclusive institution as the centre of revelatory authority.